The lipoprotein biosynthesis pathway: key to OXA-mediated carbapenem resistance in Acinetobacter baumannii - Moran Barrio, Jorgelina (2025)
Carbapenem resistance in the Gram-negative opportunistic pathogen Acinetobacter baumannii primarily stems from the overexpression of acquired class D serine β-lactamases, known as OXA carbapenemases. These enzymes exhibit weak carbapenemase activity and possess lipoprotein signal peptides. While the kinetic and structural aspects of OXA enzymes have been characterized, their biogenesis pathway has received little attention, despite potentially offering novel therapeutic targets. Here, we investigated the biosynthetic process of the OXA-58 carbapenemase in the model A. baumannii strain ATCC17978. [3H]palmitate labeling confirmed that the OXA-58 precursor is lipidated in vivo. Replacing the OXA-58 lipobox cysteine with alanine through site-directed mutagenesis demonstrated that, while the lipoprotein pathway is not essential for productive OXA-58 synthesis, it is crucial for achieving the high cellular OXA-58 levels A. baumannii needs to efficiently overcome carbapenem challenge. Lipidation significantly increased OXA-58 hydrophobicity, directing the carbapenemase to a membrane location, likely the outer membrane (OM), after periplasmic translocation. This specific localization is a critical step for accumulating the high periplasmic OXA-58 concentration necessary for carbapenem resistance. Furthermore, lipidation enabled the selective recruitment of OXA-58 into outer membrane vesicles (OMV), revealing a novel disposal mechanism for surplus OXA-58 production. In conclusion, the A. baumannii lipoprotein biosynthetic pathway facilitates both the high periplasmic OXA-58 concentration essential for a more efficient carbapenem resistance and the attendant selective removal of surplus OXA-58 production via OMV. These features were likely powerful drivers in the selection of the lipoprotein pathway for the overproduction of OXA carbapenemases among contemporary A. baumannii strains subjected to carbapenem challenge.